Family Background and School Choice in Cities of Russia and Estonia: Selective Agenda of the Soviet Past and Present - Põder, Kaire; Lauri, Triin; Ivaniushina, Valeria; Alexandrov, Daniel (Studies of Transition States and Societies, 2016)
In this article, we demonstrate the size of family background eff ects in various regions of Russia and Estonia, concentrating on urban and rural diff erences, addressing the idea that the family background effect is moderated by school level admission policies. Having common path-dependent educational institutions from the communist period, the countries diff er in both the extensiveness of the welfare state and system level school choice policies. However, we see many commonalities in both systems, especially at the urban school level. The family background eff ect is defi ned as the dependence of student achievement on family background characteristics, such as parental education, income and social status. In operationalising family background, the number of books at home and parental education are used as proxies, and its eff ect is measured as a percentage of the individual level PISA 2012 score. We contribute to the literature by studying school choice, its key characteristics and moderating eff ects by school level admission policy in an urban environment.